Can Public Flats Bridge the Gap? Housing Solutions for Low-Income Residents in Brebes - Nuraini, Rina Waliya; Niravita, Aprila; Alimuddin, Subhan Fikri; Youssef, Fatma (Universitas Negeri Semarang, 2025)
The provision of adequate housing for low-income communities (MBR) in Brebes Regency is a significant challenge in the context of rapid economic and population growth. This article examines the dynamics of the development of Simple Rental Flats (rusunawa) as an affordable housing solution for MBR. Through a qualitative descriptive approach, this study explores government policies, challenges faced, and the potential of rusunawa in improving the quality of life of the community. The results of the study indicate that although rusunawa offers accessibility, security, and comfort, there are still obstacles in the socialization and understanding of the community regarding this facility. Therefore, further efforts are needed to improve public information and participation in rusunawa management. This study is expected to provide recommendations for policy makers to create more inclusive and sustainable housing solutions.